Comparative and Contrastive Analysis of Foregrounding in English and Uzbek Literary Text in Terms of Cognitive Linguistics - Rustamovich, Achilov Oybek (Journal of Innovation in Education and Social Research, 2025)
In the article, the results identified in the field of cognitive linguistics are comparatively studied based on the analysis of English and Uzbek literary works. The article also examines the contributions of English, Russian, and Uzbek scholars to cognitive semantics.